[PP.32.09] EPISTAXIS: RELATIONSHIP WITH CLINIC BLOOD PRESSURE. (September 2016) - Bertacchini, F.; Paini, A.; Salvetti, M.; Bazza, A.; Colonetti, E.; Rosei, C. Agabiti; Verzeri, L.; Lombardi, D.; Nicolai, P.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective Background: Epistaxis and hypertension are frequent diseases in the adult population. A relationship between the increase of the blood pressure (BP) and the prevalence and incidence of epistaxis has been suggested (Kikidis et al, 2013). Design and method: Aim of our study was to analyze blood pressure changes in patients with active or recent onset epistaxis (<12 hours) from admission to the emergency department (ED) to discharge. Patients and methods: 126 consecutive subjects (84 males, age range 15–93 years, mean age 67 ± 17 years) admitted to the ED (April 2014-February 2015) with primary epistaxis, were prospectively evaluated. BP was measured with an automatic device (OMRON MT10-E) in accordance to ESH-ESC guidelines 2013; measurements were performed at admission to the ED and 30 minutes after the ear, nose and throat (ENT) specialist visit (and possible hemostasis). Results Results: a diagnosis of hypertension was present in 68% of subjects; 75% of them were on antihypertensive treatment, 35% of them reported adequate BP control, 17% had diabetes mellitus and 25% dyslipidemia. A statistically significant reduction in BP was observed from admission to the ED and to the end of ENT evaluation (from 142 ± 21/84 ± 13 mmHg to 135 ± 21/81 ± 13 mmHg, p = 0.001), while no significant changes were observed in heart rate (from 76 ± 15 to 72 ± 13 b/min). Conclusions Conclusions: results obtained in this group of patients with primary epistaxis show a prevalence of hypertension similar to that of a general population. An accurate BP measurement shows a significant reduction at the end of the ENT specialist evaluation compared to baseline measurement, in both hypertensive and normotensive subjects.